IBM z/OS V2R2 user interfaces - Winnard, Keith; Hering, Paul-Robert (IBM redbooks, 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the User Interface areas of IBM z/OS® V2R2. This publication is one in a series of IBM Redbooks publications that take a modular approach to providing information about the updates within z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic It is our hope that this approach is useful. We value your feedback.